The Occupational Performance Measure of Food Activities: Item Pool Development and Measurement Properties. (February 2014) - Plastow, Nicola Ann; Spiliotopoulou, Georgia; Atwal, Anita; Gilhooly, Mary
Introduction: Occupational therapists have the knowledge and skills to improve nutritional risk in community-living older adults by improving performance of food-related occupations. However, few tools are available to evaluate these interventions. We developed the first item pool that measures community-living older adults' occupational performance of food activities. Method: In Phase 1 of the research we developed an item pool within a qualitative exploratory study with five older adults. In Phase 2 we designed the Occupational Performance Measure of Food Activities. In Phase 3 we formally assessed the measurement properties of the 15-item measure, using survey responses from 77 community-living older adults. Construct validity, reliability, and utility were evaluated. Findings: A 13-item measure of the occupational performance of food activities showed acceptable validity and reliability in three subscales (Cronbach's α ranged from .70 to .75). The item pool demonstrated good utility. We had comparable results for administration via self-completion survey (n = 38) and interview (n = 39). Conclusion: This unique item pool showed promising validity and reliability for the measurement of the occupational performance of food activities. Occupational therapists are cautioned against modifying existing measurement tools without thorough testing of the resulting new measure of occupational performance.